Developing a Pictorial Sisterhood Method in collaboration with illiterate Maasai traditional birth attendants in northern Tanzania. Issue 1 (October 2016) - Roggeveen, Yadira; Schreuder, Renske; Zweekhorst, Marjolein; Manyama, Mange; Hatfield, Jennifer; Scheele, Fedde; van Roosmalen, Jos
Abstract: Objective: To study whether data on maternal mortality can be gathered while maintaining local ownership of data in a pastoralist setting where a scarcity of data sources and a culture of silence around maternal death amplifies limited awareness of the magnitude of maternal mortality. Methods: As part of a participatory action research project, investigators and illiterate traditional birth attendants (TBAs) collaboratively developed a quantitative participatory tool—the Pictorial Sisterhood Method—that was pilot‐tested between March 12 and May 30, 2011, by researchers and TBAs in a cross‐sectional study. Results: Fourteen TBAs interviewed 496 women (sample), which led to 2241 sister units of risk and a maternal mortality ratio of 689 deaths per 100 000 live births (95% confidence interval 419–959). Researchers interviewed 474 women (sample), leading to 1487 sister units of risk and a maternal mortality ratio of 484 (95% confidence interval 172–795). Conclusion: The Pictorial Sisterhood Method is an innovative application that might increase the participation of illiterate individuals in maternal health research and advocacy. It offers interesting opportunities to increase maternal mortality data ownership and awareness, and warrants further study and validation.